Analysis of Analysis of Teacher Competence in Music Learning at TK Tunas Bangsa, Sinar Harapan Village, Tungkal Jaya District, Musi Banyuasin Regency - Kompri; Wahyu Lestari; Mastikawati; Fitriah (Journal of Early Childhood Development and Education, 2026)
Background: Teacher competence in early childhood learning plays a crucial role in stimulating children’s creativity and developmental abilities. However, at TK Tunas Bangsa Desa Sinar Harapan, the competence of teachers in conducting music education remains relatively low compared to other subjects. Teachers frequently replace music lessons with visual arts activities such as drawing, indicating limited mastery of musical concepts and teaching strategies Objective: This study aims to analyze the level of teacher competence in music learning and identify the factors that influence the replacement of music lessons with visual arts. The scope of this paper focuses on pedagogical competence, mastery of teaching materials, learning implementation, and teachers’ readiness to deliver music-related activities. Methods: This research employs a qualitative descriptive method. Data were collected through interviews with teachers, classroom observations, and documentation review to obtain a comprehensive understanding of music learning practices in the classroom. Results: The findings reveal that teachers have limited skills in vocal techniques, rhythm instruction, and the use of simple musical instruments. As a result, teachers tend to avoid music lessons and shift to drawing activities, which they perceive as easier to manage. The study also shows that the lack of training, insufficient learning media, and minimal exposure to music pedagogy significantly affect teachers’ competence. Conclusion: The study concludes that teacher competence in music education at TK Tunas Bangsa is still inadequate and requires strengthening through targeted training, provision of musical learning resources, and continuous professional development. Improved competence is expected to encourage teachers to implement meaningful and consistent music learning in early childhood education.